THE EFFECT OF INFLATION, COMPANY SIZE AND DEBT TO EQUITY RATIO ON STOCK UNDERPRICING MODERATED BY UNDERWRITER REPUTATION IN COMPANIES CONDUCTING INITIAL PUBLIC OFFERINGS (IPOs) ON THE INDONESIAN STOCK EXCHANGE FROM 2021 TO 2024 - Firmansyah Firmansyah; Eka Yulianti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study evaluates the impacts of inflation, firm size, and leverage, proxied by the debt-to-equity ratio, on IPO underpricing among companies listed on the Indonesia Stock Exchange during the 2021–2024 period., with underwriter reputation posited as a moderating construct. Employing a quantitative design, secondary data were extracted from corporate financial disclosures and capital market sources. The final sample comprised 140 underpriced IPO firms selected through purposive sampling. The empirical investigation employed multiple linear regression and Moderated Regression Analysis (MRA). The results demonstrate that none of the explanatory variables exert statistically significant partial effects on IPO underpricing. Furthermore, underwriter reputation neither directly influences underpricing nor moderates the relationships between inflation, firm size, leverage, and IPO underpricing. Collectively, the explanatory variables also fail to exhibit a significant joint effect. These outcomes suggest that IPO underpricing in Indonesia is driven by determinants beyond the macroeconomic conditions and firm-specific financial attributes examined herein.